PRIMARY OUTCOME MEASURES IN PEDIATRIC SEPTIC SHOCK: SYSTEMATIC REVIEW - Setiawati, Ferianis; Prima Dewi, Anis (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Sepsis is a major cause of mortality in pediatric populations, with 22 cases per 100,000 live births in infants and 2,202 cases per 100,000 live births in neonates, causing an annual burden of 1.2 million cases. There is currently no consensus regarding the most appropriate to measure the primary outcome of pediatric septic shock. Objective: The aim of this study was to determine the primary outcome that should be assessed in pediatric patients who experience sepsis shock Methods: Based on Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), we searched literature from several databases (PubMed, ScienceDirect, and Web of Science) following PRISMA guidelines. The following keywords are used: ((Primary) AND (Outcome) AND (Measure) OR (Indicator) AND (Pediatric) OR (Childern) AND (Septic) AND (Shock)). Manual searches are also conducted to get relevant articles that meet the mentioned criteria. Data were extracted based on author, year, study design, sample size, results and discussion. Results: In this systematic review, we found a total of five studies, with three types of prospective studies and two retrospective studies. A total of 5.164 cases were involved in the study, with a range years 2014 to 2023. Of the five studies, all discussed that mortality was the primary outcome measured in pediatric patients with septic shock. Other indicators that can be measured as outcomes in patients are length of hospitalization, clearance from lactic acid, and occurrence of multiple organ disfunction. Conclusion: In pediatric patients with sepsis shock there are several primary outcomes that can be assessed. Some literature suggests that mortality is a major outcome to be considered.